Isolation and Characterization of Endophytic Bacteria from Curcuma Aeruginosa Roxb As Antibacterial Candidates Againts Pneumonia - Arti Wahyu Utami; Firman Rezaldi; Rifkarosita Putri Ginaris; Jihan Nabilla; Bramantyo; Puput Setiawati; Zulfania Shandra Fatikha; Nanik Pujiastuti; Dwi Wahyuni (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to isolate and characterize endophytic bacteria from black turmeric rhizomes (Curcuma aeruginosa Roxb) and test their potential as antibacterial agents against Streptococcus pneumoniae. This experimental research began with the isolation of endophytic bacteria from surface-sterilized black turmeric rhizomes. The obtained pure isolates were characterized macroscopically (colony shape, margin, elevation, pigment) and microscopically (cell shape, Gram staining). The growth curve of potential isolates was determined, and antibacterial activity was tested using the disc diffusion method against S. pneumoniae, with ciprofloxacin as a positive control. Six endophytic bacterial isolates (PS1, PS2, PS3, PS4, PS5, PS6) were successfully isolated, showing variations in colony morphology, and all were classified as Gram-negative bacilli. All isolates exhibited strong antibacterial activity against Streptococus pneumoniae, with inhibition zone diameters ranging from 15.3 mm to 20.6 mm. Black turmeric rhizomes (Curcuma aeruginosa Roxb) harbor diverse endophytic bacteria with significant potential as antibacterial agents against the pneumonia pathogen, Streptococcus pneumoniae.